The Impact Of Work Discipline On Employee Performance At STIE Hidayatullah Depok - Husain, Muh. Ali; Muldani, Veri (Transforma Jurnal Manajemen, 2024)
This study aims to determine whether there is an influence between work discipline and employee performance at STIE Hidayatullah Depok. The population in this study were all employees at the STIE Hidayatullah Depok office, and the sample was determined purposively. The research method used in this study is a quantitative descriptive method. Based on the results of the analysis that has been carried out, it shows that the work discipline variable has a positive effect on employee performance at STIE Hidayatullah Depok. The magnitude of the contribution of work discipline to employee performance can be said to be significant from the analysis that has been carried out at STIE Hidayatullah Depok.